EFEKTIVITAS PENGGUNAAN QUIZIZ SEBAGAI MEDIA EVALUASI PEMBELAJARAN DI SMK NEGERI 26 JAKARTA - Almasa Bahira (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The aim of this research is to find out how effective Quizizz is as a learning evaluation tool at SMK Negeri 26 Jakarta. This research uses a qualitative approach with an open questionnaire, and data is collected through in-depth questionnaires distributed to students. The research results show that Quizizz has several advantages, such as increasing student motivation and involvement in the evaluation process, providing direct feedback that helps students improve their understanding, and making it easier for teachers to track and analyze student learning outcomes more easily. However, technical problems related to internet connectivity and initial adaptation to digital platforms were some of the problems discovered in this research. Overall, Quizizz has proven to be an innovative evaluation tool that helps students at SMK Negeri 26 Jakarta learn. Recommendations are given to develop modern learning media in the modern era and maximize profits.